ANALISIS KUALITAS KOMPOS PERTANIAN DARI LIMBAH RUMAH TANGGA - Hasan Ibrahim; Rinda Yanti; Setya Dharma; Harmailis Harmailis (Partner, 2021)
The method of making compost is easy to apply on a household scale. However, the lack of knowledge and skills about making compost made causes the quality of the compost produced to be not optimal. This study analyzed the quality of household waste compost using the Heap method (curing) and Practical Composter with compost quality indicators SNI 19-7030-2004 in terms of pH, water content, nutrient content of N, P, K, Ca, Mg, C/N ratio. Furthermore, the data were processed by statistical analysis of the comparative t test. The results showed that the composting of household waste using the practical composter method produced compost with higher N, P, K, and C content than the Heap method and the SNI 19-7030-2004 standard. However, the elemental content of Ca, Mg, and Water Content is lower than the SNI standard. pH and C/N of compost with composter method according to SNI standard. Keywords: Composter, Waste, Nutrient Quality, Sustainable